Guion turístico del centro histórico de Latacunga (zona 1) - Arcos Navas, Mishell Alejandra (2024)
This project called "Tourist script of the historic center of Latacunga (zone 1)" describes the tourist attractions, tangible and intangible cultural heritage. The elaboration of the tourist script can contribute to transmit to the visitors the history, the architectural, cultural, artistic and landscape value of the attractions; at the same time, it can be transformed into a tool for the creation of routes and tours within the historical center being thus beneficial for the tourist sector. The general objective of the research project is to describe the historic center of Latacunga through the development of a tourist guide that serves as a validated and standardized instrument for the exercise of the different tourist activities, to obtain the desired result, 3 specific objectives were proposed, through an analytical, deductive and qualitative approach in order to identify, interpret, collect and analyze the data obtained. In the first objective, a field and bibliographic research was carried out, using the synthetic methodology to point out the characteristics of the political, economic, social and tourist areas of the historical center of Latacunga, with the help of primary and secondary sources such as scientific articles, theses, pages and an interview at UNESCO Quito.